Ghosts in the Neighborhood Why Japan Is Haunted by Its Past and Germany Is Not - Hatch, Walter (Weiser Center for Emerging Democracies, 2023)
Germany, which brutalized its neighbors in Europe for centuries, has mostly escaped the ghosts of the past, while Japan remains haunted in Asia. The most common explanation for this difference is that Germany knows better how to apologize; Japan is viewed as "impenitent." Walter F. Hatch rejects the conventional wisdom and argues that Germany has achieved reconciliation with neighbors by showing that it can be a trustworthy partner in regional institutions like the European Union and NATO; Japan has never been given that opportunity (by its dominant partner, the U.S.) to demonstrate such an ability to cooperate. This book rigorously defends the argument that political cooperation-not discourse or economic exchange-best explains Germany's relative success and Japan's relative failure in achieving reconciliation with neighbors brutalized by each regional power in the past. It uses paired case studies (Germany-France and Japan-South Korea; Germany-Poland and Japan-China) to gauge the effect of these competing variables on public opinion over time. With numerous charts, each of the four empirical chapters illustrates the powerful causal relationship between institution building and interstate reconciliation.